2017
DOI: 10.3168/jds.2016-12489
|View full text |Cite
|
Sign up to set email alerts
|

Performance strategies affect mammary gland development in prepubertal heifers

Abstract: In Brazil, the majority of dairy cattle are Holstein × Gyr (H×G). It is unknown whether excessive energy intake negatively affects their mammary development to the same extent as in purebred Holsteins. We hypothesized that mammary development of H×G heifers can be affected by dietary energy supply. We evaluated the effect of different average daily gains (ADG) achieved by feeding different amounts of a standard diet during the growing period on biometric measurements, development of mammary parenchyma (PAR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Although important studies on the nutrient requirements of crossbred dairy cattle ( Bos taurus × Bos indicus ) have been published [ 96 , 97 , 98 ], data on heifers are still scarce. Since 2016, heifer studies have been performed to better understand the effects of ADG and supply of nutrients on mammary gland development in prepubertal and pubertal crossbred heifers [ 69 , 99 , 100 ]. Moreover, other studies have evaluated the effects of gestation days on the body and conceptus composition and nutrient use by pregnant crossbred cows [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although important studies on the nutrient requirements of crossbred dairy cattle ( Bos taurus × Bos indicus ) have been published [ 96 , 97 , 98 ], data on heifers are still scarce. Since 2016, heifer studies have been performed to better understand the effects of ADG and supply of nutrients on mammary gland development in prepubertal and pubertal crossbred heifers [ 69 , 99 , 100 ]. Moreover, other studies have evaluated the effects of gestation days on the body and conceptus composition and nutrient use by pregnant crossbred cows [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data support the evidence that a restricted window of susceptibility, such as puberty, may be sufficient to promote the development of mammary epithelial tissue. Moreover, other authors have produced evidence that overfeeding prepubertal heifers with a high‐energy diet reduced mammary epithelium mass at puberty and negatively affected mammary development by decreasing both MEC proliferation in areas of active ductal expansion and the mass of fat‐free mammary epithelial tissue …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other authors have produced evidence that overfeeding prepubertal heifers with a high-energy diet reduced mammary epithelium mass at puberty and negatively affected mammary development by decreasing both MEC proliferation in areas of active ductal expansion and the mass of fat-free mammary epithelial tissue. 47,48 To determine whether the reduction in alveolar epithelial tissue, observed in the present study, was due to either a decreased proliferation or an increased apoptosis of epithelial cells, measurements of Ki67 expression and TUNEL experiments have been used. 34 Although Ki67 is expressed in early pregnancy, we did not observe a significant difference in Ki67 mRNA content between OD and CD-fed rabbit mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Considering an ADG between 600 to 700 g/d of the supplemented groups, the absence of effect in the mammary gland development of crossbred animals is different from results observed in other studies. [58] observed that ½ Holstein × Gyr animals with an ADG of 0.9 kg/d showed impaired mammary gland development. This difference may have occurred due to the genetic merit of animals use in both studies.…”
Section: Plos Onementioning
confidence: 97%